Development of loyalty programs for sellers of the main Russian marketplaces - Kholmovsky, S. G. (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. An oligopolistic situation has developed in the Russian marketplace market, where two main market players occupy a dominant position. In the context of the observed slowdown in the growth of the e-commerce market, the main efforts of players in the future will inevitably be aimed at retaining old customers and sellers rather than attracting new participants, whose number is limited. The loyalty programs offered by marketplaces to trade participants are designed to ensure the commitment of sellers to specific electronic platforms. Goal. The study aims to identify the main features and parameters of loyalty programs offered by marketplaces for their sellers. Materials and methods. The methodology of the conducted research is based on the use of general scientific research methods of analysis and synthesis, generalization, statistical, etc. The information base for the study was data from analytical reviews of the Russian market, marketplaces reporting data, and publications by Russian scientists. Results and discussion. The article examines the development trends of Russian e-commerce market, analyzes the share of the largest marketplaces in it, and identifies the features of the current stage of development of the e-commerce market, which consist in the oligopolistic structure of the marketplace market. The historical experience of cooperation with marketplaces of sellers of platforms is analyzed, the peculiarities of loyalty on marketplaces in comparison with traditional retail trade are determined, the degree of loyalty of suppliers to individual electronic platforms is revealed. The article examines the elements of loyalty programs offered by the largest Russian marketplaces, their focus and potential benefits for participants, and examines the transformation of these programs over time. Conclusion. With account of the development of digital technologies the main directions of changing loyalty programs of marketplaces are proposed